Assessing the validity of QRISK3 in predicting cardiovascular events in systemic lupus erythematosus. Issue 1 (22nd February 2022) - Zhu, Lisa; Singh, Manpreet; Lele, Sonia; Sahakian, Lori; Grossman, Jennifer; Hahn, Bevra; McMahon, Maureen
Abstract : Objectives: Traditional cardiovascular risk calculators such as the Framingham Risk Score (FRS) have been shown to underestimate risk in patients with SLE. The QRISK3 calculator is unique in including SLE and corticosteroid use as risk factors. This study aims to assess the validity of QRISK3 compared with other cardiovascular risk models in a cohort of patients with SLE in the USA. Methods: We studied a prospective cohort of 366 adult patients with SLE without history of any cardiovascular event and followed them for 10 years. We compared the diagnostic performance of QRISK3 with FRS, modified FRS, Atherosclerotic Cardiovascular Disease (ASCVD), and Predictors of Risk for Elevated Flares, Damage Progression and Increased Cardiovascular Disease in Patients with SLE (PREDICTS). Results: Sixty-four of the 366 patients (17.4%) experienced at least one cardiovascular event during the 10-year follow-up period. Of these patients 45% had a QRISK3 score >10%, whereas 20.5% of patients who did not have an event had a QRISK3 score >10% (p<0.001). The corresponding numbers for FRS, modified FRS, ASCVD and PREDICTS were 11.0% vs 7.2% (p=ns), 40.6% vs 28.0% (p=0.05), 12.2% vs 5.9% (p=ns), and 77% vs 32.1% (p<0.001), respectively. The areas under the receiver operating characteristic curve using QRISK3 >10% and high-risk PREDICTS were both larger than those using ASCVD >10%, FRS >10% and modified FRS >10%. Conclusions: Both QRISK3 and PREDICTS demonstrated better performance in predicting risk of cardiovascular disease in this cohort of patients with SLE compared with FRS, modified FRS and ASCVD.